Nanomedicine for Imaging and Therapy of Pancreatic Adenocarcinoma - Brachi, Giulia; Bussolino, Federico; Ciardelli, Gianluca; Mattu, Clara (Frontiers in Bioengineering and Biotechnology, 2019)
Pancreatic adenocarcinoma has the worst outcome among all cancer types, with a 5-year survival rate as low as 10%. The lethal nature of this cancer is a result of its silent onset, resistance to therapies, and rapid spreading. As a result, most patients remain asymptomatic and present at diagnosis with an already infiltrating and incurable disease. The tumor microenvironment, composed of a dense stroma and of disorganized blood vessels, coupled with the dysfunctional signal pathways in tumor cells, create a set of physical and biological barriers that make this tumor extremely hard-to-treat with traditional chemotherapy. Nanomedicine has great potential in pancreatic adenocarcinoma, because of the ability of nano-formulated drugs to overcome biological barriers and to enhance drug accumulation at the target site. Moreover, monitoring of disease progression can be achieved by combining drug delivery with imaging probes, resulting in early detection of metastatic progression. This review describes the latest development of theranostic formulations designed to concomitantly treat and image pancreatic cancer, with a specific focus on their interaction with physical and biological barriers.